Sumoylation of Notch1 represses its target gene expression during cell stress - Antila, Christian J. M. (Cell Death Differ, 2018)
The Notch signaling pathway is a key regulator of stem cells during development, and its deregulated activity is linked to developmental defects and cancer. Transcriptional activation of Notch target genes requires cleavage of the Notch receptor in response to ligand binding, production of the Notch intracellular domain (NICD1), NICD1 migration into the nucleus, and assembly of a transcriptional complex. Post-translational modifications of Notch regulate its trafficking, turnover, and transcriptional activity. Here, we show that NICD1 is modified by small ubiquitin-like modifier (SUMO) in a stress-inducible manner. Sumoylation occurs in the nucleus where NICD1 is sumoylated in the RBPJ-associated molecule (RAM) domain. Although stress and sumoylation enhance nuclear localization of NICD1, its transcriptional activity is attenuated. Molecular modeling indicates that sumoylation can occur within the DNA-bound ternary transcriptional complex, consisting of NICD1, the transcription factor Suppressor of Hairless (CSL), and the co-activator Mastermind-like (MAML) without its disruption. Mechanistically, sumoylation of NICD1 facilitates the recruitment of histone deacetylase 4 (HDAC4) to the Notch transcriptional complex to suppress Notch target gene expression. Stress-induced sumoylation decreases the NICD1-mediated induction of Notch target genes, which was abrogated by expressing a sumoylation-defected mutant in cells and in the developing central nervous system of the chick in vivo. Our findings of the stress-inducible sumoylation of NICD1 reveal a novel context-dependent regulatory mechanism of Notch target gene expression.